A New Model for Job Creation in Armenia : Promoting More Effective Accumulation, Competition, and Connectivity - Bartsch, Ulrich (World Bank, Washington, DC, 2015)
In Armenia, more effective accumulation, together with greater competition and better connectivity with the rest of the world, will increase pressures on firms to compete and innovate and will thus reinvigorate job creation. In order to more effectively channel savings into investment in those industrial sectors with the best potential for growth and employment creation, a more sophisticated financial system is required. A recently released World Bank report1 finds that Armenias State Commission for the Protection of Competition (SCPEC) needs to be given better tools to carry out its work, and it also needs to shift its focus from price levels to more vigorously pursuing anticompetitive conduct. A liberalization of aviation would boost growth and job creation by better connecting people, ideas, and markets.